Growth analysis of tomato for industrial processing as a function of nitrogen doses - Costa, Leonardo Correia [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP]; Ribas, Rodolfo Gustavo Teixeira; Dutra, Alexson Filgueiras [UNESP]; Rocha, Antonio Márcio Souza [UNESP]; Barbosa, José Carlos [UNESP] (Southern Cross Publishing, 2020)
Nitrogen (N) is considered to be the nutrient that most affects plant growth. Understanding this mechanism helps in crop management and planning. This study analyzes the growth of tomato plants (Heinz 9553) for industrial purposes as a function of N doses (0, 60, 120 and 180 kg ha-1). The experiment was carried out from April to August 2015, in Barretos, São Paulo State, Brazil. The experimental design was a randomized blocks, in plots subdivided in time, with three replicates. Growth assays were performed at 14, 28, 42, 56, 70, 84, 96, 112 and 126 days after transplanting (DAT). Fertilization with 180 kg ha-1 N provided greater leaf area, leaf dry mass, shoot dry mass (leaves + stems), fruit dry mass, total dry mass, leaf area index, leaf area ratio and leaf mass ratio at the end of the cycle. The lowest relative growth rate and specific leaf area were verified with 180 kg ha-1. For all N doses, the absolute growth rate was small up to 56 DAT and, subsequently, N doses promoted distinct increases in the index.
Keywords: Growth analysis; Nitrogen fertilization; Solanum lycopersicum